UNMASKING LINGUISTIC POWER DYNAMICS: EXPLORING POLITENESS VIOLATIONS IN THE “FERDI SAMBO” COURTROOM - Sari, Yulnada; Aritini, Luh Putu; Kusuma, I Putu Indra (STKIP Persada Khatulistiwa Sintang, 2025)
In the courtroom, all participants are expected to cooperate fully to clarify the case. This research aimed to investigate the types of politeness violations committed by the participants in the Ferdi Sambo case and the causes of these violations. The participants in this study included judges, the defendant, witnesses, advocates, and public prosecutors. This research employed a qualitative-descriptive approach. The techniques for analyzing the data included identification, data presentation, and conclusion drawing. During data identification, the violations were classified using Leech's (1983) politeness strategy theory. The findings revealed that the types of politeness violations included refusal, interruption, sarcasm, emotional outbursts, and non-verbal cues. Additionally, the causes of these violations were attributed to the participants' mood, emotions, and the pressure they experienced during the trial. This research provides significant benefits, particularly for English students, by enhancing their cultural awareness, professional communication skills, and conflict resolution abilities. Understanding politeness norms can help students become more aware of cultural differences in communication, which is essential for effective interaction in diverse contexts.Keywords: Ferdi Sambo Case; Politeness; Violation; Courtroom;